2004
DOI: 10.1161/01.str.0000140740.19421.fe
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Genetic Profiles in Subjects With History of Ischemic Stroke

Abstract: Background and Purpose-Proinflammatory genetic profiles, resulting from the combination of single nucleotide polymorphisms in genes encoding inflammatory molecules, may contribute to the development and progression of cardiovascular diseases. We evaluated the association between history of ischemic stroke and genetic profiles determined by the synergistic effects of polymorphisms in genes encoding prototypical inflammatory proteins. Methods-The study included 237 individuals with history of ischemic stroke and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 36 publications
10
100
0
4
Order By: Relevance
“…However, this association was not replicated in the subsequent larger study 16 . The higher prevalence of MCP-1-2518*G homozygotes was observed in patients with history of stroke 17 and myocardial infarction 4 . …”
Section: Atherosclerosis and Myocardial Infarction (Mi)mentioning
confidence: 88%
“…However, this association was not replicated in the subsequent larger study 16 . The higher prevalence of MCP-1-2518*G homozygotes was observed in patients with history of stroke 17 and myocardial infarction 4 . …”
Section: Atherosclerosis and Myocardial Infarction (Mi)mentioning
confidence: 88%
“…Base on the inclusion criteria, 7 case-control studies with full-text were included in this meta-analysis (Revilla et al, 2002;Balding et al, 2004;Flex et al, 2004;Chamorro et al, 2005;Lalouschek et al, 2006;Banerjee et al, 2008;Tong et al, 2010) and 14 studies were excluded. The flow chart for the study selection is summarized in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three indipended studies have shown that 6A/6A genotype is associated with greater carotid intima-media thickness and higher rate of carotid stenosis (Nagase and Woessner 1999;Gnasso et al 2000;Rauramaa et al 2000). On the other hand, some studies have shown increased risk of stroke in 5A homozygotes (Flex et al 2004). Although the mechanisms leading to the stroke are likely to be complex, the rupture of atherosclerotic plaque due to increased MMP3 expression may play a role.…”
Section: ; Ye 2006mentioning
confidence: 99%
“…The risk for developing cardiovascular (CV) event is 5-30 folds higher in patients with end-stage renal disease than in the general population (Foley and Parfrey 1998;Cheung et al 2000;Locatelli et al 2001;Pernod et al 2006). Since traditional risk factors could not explain high prevalence of cardiovascular disease (Foley et al 1996;Longenecker et al 2002;Pernod et al 2006), many reports have suggested a role of non-traditional risk factors in pathogenesis of CVD, including gene polymorphism of matrix metalloproteinase (MMP) (Humphries et al 2002;Beyzade et al 2003;Flex et al 2004;Beilby et al 2005;Koch et al 2010).…”
Section: Introductionmentioning
confidence: 99%